2020
DOI: 10.1177/1362168820913978
|View full text |Cite
|
Sign up to set email alerts
|

Language teachers’ reported first and second language use: A comparative contextualized study of England and Spain

Abstract: There is now extensive theoretical and empirical literature on the place of the first language (L1) and the second language (L2) in the foreign language (FL) classroom. Although this body of work includes related teacher beliefs and practices, less attention has been paid to the factors that may influence these practices across different national contexts. Through an extensive survey of secondary school teachers of a FL in Spain and England we investigated teachers’ reported L1/L2 practices and the possible in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Georgious and Krulatz (2018) reported from surveys that 92% of the 24 in-service elementary and middle-school EFL teachers in Norway employed the L1 in L2 teaching. In the same way, data from questionnaires provided to foreign language teachers in England and Spain by Molway, Arcos, and Macaro (2022) showed that both groups used their corresponding L1 in classes. Among the reasons teachers use the L1 for L2 teaching, Taşçı and Ataç (2020) obtained the following L1 functions from semi-structured interviews and class observations of three primary school teachers in Turkey: to give instructions, to teach grammar, to teach difficult vocabulary, to manage the classroom, to check understanding, to draw students' attention, to elicit, and to provide feedback.…”
Section: Introductionmentioning
confidence: 83%
“…Georgious and Krulatz (2018) reported from surveys that 92% of the 24 in-service elementary and middle-school EFL teachers in Norway employed the L1 in L2 teaching. In the same way, data from questionnaires provided to foreign language teachers in England and Spain by Molway, Arcos, and Macaro (2022) showed that both groups used their corresponding L1 in classes. Among the reasons teachers use the L1 for L2 teaching, Taşçı and Ataç (2020) obtained the following L1 functions from semi-structured interviews and class observations of three primary school teachers in Turkey: to give instructions, to teach grammar, to teach difficult vocabulary, to manage the classroom, to check understanding, to draw students' attention, to elicit, and to provide feedback.…”
Section: Introductionmentioning
confidence: 83%
“…The first language did not have any role in teaching practices since the L1 translation was assumed as closely connected to the grammar-translation method. Molway et al [23], argued that while the visible difference between the direct method and grammar-translation was the former's avoidance of the L1, "the underlying theoretical stance was that the vocabulary and structures of the language could be learned implicitly or inductively rather than explicitly or by comparison with the L1" [23, p. 644]. When the grammar-translation approach lost its popularity as a practical language teaching method, many linguists, teachers, and instructors started arguing about using learners' first language in foreign language classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This development priority appears to be driven both by changing assessment structures and a strongly articulated belief, in line with current policy and research (Macaro et al, 2016), that communicative competence is the most valuable of the language skills and the key to developing pupils' confidence and self-efficacy. Recent research suggests that teachers in England rarely use L2 as the dominant means of communication in the classroom, which may inhibit the development of oral interaction skills (Molway, Arcos & Macaro, 2020). Fulfilling the aspiration to develop students' spoken language is therefore likely to require a shift in pedagogy both in terms of task design (teachers will need to create increased opportunities for student output in the L2) but also in terms of the teachers' own modelling of the language to create a target language rich classroom community.…”
Section: [Table 8 Around Here]mentioning
confidence: 99%
“…Given the prevalence of the target to improve pupils' speaking skills in the data collected at individual teacher level, it is striking that only three of the twelve HoDs made explicit mention of speaking within their MFLDIPs. Laurel HoD is the only one to explicitly mention increasing teachers' use of the target language as a development aim, which is surprising given that existing research suggests a target language rich environment is key to the development of students' speaking skills (Crichton, 2009;Molway, Arcos & Macaro, 2020).…”
Section: Mfl Departments' Subject Development and Improvement Plansmentioning
confidence: 99%